Political Economy of Federalism: Insights from Data on Guns, Goons and Gold - Banaag, Miann S (Archīum Ateneo, 2017)
Even deeper decentralization (de-concentration and devolution) in the Philippines will likely face chronic challenges in local governance. Emerging evidence from several decades of policy experience from the implementation of the Local Government Code suggests that weak governance and traditional politics – perhaps epitomized by the adage “guns, goons and gold” – still frustrates strong and inclusive development outcomes in the entire country. If federalism is to succeed, it will need to address these challenges and create more effective mechanisms to help new federal jurisdictions and sub-jurisdictions transition towards better governance and stronger development outcomes. As a contribution to the ongoing discussions on decentralization and local governance, this paper examines some of the possible governance and political economy issues in rolling out federalism reforms. This paper explores the risks and potential of the current governance structure of the country upon transition to a federal form of government. To help illustrate challenges and opportunities in this transition, this paper examines the cases of three proposed states and the potential for successful federalism reforms by highlighting three areas: guns and goons (dynasties, conflict and private armies) and gold (wealth and socio-economic variables).